Анализ систем на основе дифференциальных уравнений первого порядка - Северин, Валерий Петрович (НТУ "ХПИ", 2012)
Изложены теория и методы решения дифференциальных уравнений первого порядка. Рассмотрены основные понятия теории дифференциальных уравнений; теория дифференциальных уравнений первого порядка, интегрируемых в квадратурах; вопросы существования решения уравнений первого порядка; теория дифференциальных уравнений, не разрешенных относительно производных. Даны задания для практических занятий и самостоятельной работы студентов. Предназначено для студентов технических специальностей.

The theory and methods for solving first-order differential equations are presented. The basic concepts of the theory of differential equations, the theory of first-order differential equations that are integrable in quadratures, the existence of solutions of first-order equations, the theory of differential equations not solved with respect to derivatives are considered. The tasks for practical classes and independent work of students are given. It is intended for students of technical specialties.
Analysis of systems based on differential equations of the first order
Keywords: дифференциальные уравнения; теория дифференциальных уравнений; решение дифференциальных уравнений; теорема Коши; differential equations; theory of differential equations; solution of differential equations; Cauchy's theorem